HIGH CONSERVATION VALUE (HCV) CONSIDERATION IN THE EXTRICATION OF FOREST AREA FOR PALM PLANTATION - Muhdar, Muhamad; Retno S., Haris; Sopialena, Sopialena (Tadulako University, 2019)
Planting activities are undergoing in the area of former forest with mechanism of extrication of forest area or non-forest area that commonly has high conservation value or known as High Conservation Value (HCV). However, the extrication of forest area for Palm Plantation has eroded the presence of forest with HCV disrupting ecosystem balance and harming the wellbeing of current and next generations. Legal system does not specifically regulate the limit of application for the use of forest area for palm plantation through the mechanism of forest extrication. Legal provisions at the national and regional levels encounter a difficulty accommodating the existence of area with HCV, especially in terms of regional spatial plans. Moreover, the obscurity of forest distribution and non-forestry areas with HCV also complicates the regulation at the level of imperative provisions.